Asymmetry as Fairness: Reversing a Peremptory Trend - Anna Roberts (Washington University Law Review, 2015)
A recent Ninth Circuit decision, prohibiting peremptory challenges on the basis of sexual orientation, reveals the continuing evolution of the Batson doctrine. Meanwhile, contrary judicial voices demand the abolition of the peremptory challenge. This Article uncovers two phenomena that militate against abolition of the peremptory challenge, and in favor of allowing Batson’s evolution. First, the justifications for abolition apply asymmetrically to prosecution and defense, suggesting that an asymmetrical approach is more apt. Second, the states historically adopted an asymmetrical approach—unequal allocation of peremptory challenges to prosecution and defense—and yet many state legislatures have recently abandoned asymmetry, with some legislators declaring that there are no reasons not to. This Article supplies those reasons, demonstrating that asymmetrical allocation of peremptory challenges not only brings benefits in the context of jury selection but also may help resist tendencies elsewhere in the criminal justice system to equate asymmetry with unfairness, and thus to erode foundational protections.
Keywords: Peremptory challenge; Sexual orientation; Batson v. Kentucky; Batson; Criminal Law; Jury selection; Voir dire; Criminal Procedure